Design of a Mobile Application to Improve the Therapy Process in Children with Autism - Iparraguirre-Villanueva, Orlando (2023)
Autism is a spectrum disorder that affects communication and social interaction. It has increased in recent decades, especially among children, and has had a significant impact on their lives, necessitating attention and appropriate support. A prototype mobile application was developed using the Scrum methodology, which allows for flexibility, adaptability, incremental delivery, and quality, as well as continuous improvement. The result obtained was a prototype with a design and features that facilitate patient and specialist access to healthcare areas. The quality of the prototype was evaluated by experts, who assessed its efficiency, usability, design, and functionality and obtained an average score of 4.61. This indicates that, according to the established quality range, it is high. In conclusion, the prototype enhances the therapeutic process for children with autism. It is efficient, easy to use, and has good functionality and an attractive design. This provides a solution that facilitates patients’ access to health services for their well-being.